Genetic analysis and heterosis breeding of seed yield and yieldattributing traits in Indian mustard (Brassica juncea (L.) Czern & Coss.) - Sanghamitra Rout; Suvendu Kumar Roy; Rupsanatan Mandal; Saurav Singla; Mehdi Rahimi; Bijaya Sur; Naderla Umamaheswar; Moumita Chakraborty; Lakshmi Hijam; Sahanob Nath; Manoj Kanti Debnath; Tulsi Saran Ghimiray (Scientific Reports)
Abstract This study aimed to assess the genetic basis and combining ability of 10 morphological traits in Indian mustard. The experiment involved eight parent lines and 28 crosses derived from a half-diallel mating design. Combining ability analysis is vital for identifying parents and hybrids with favorable genetic effects to enhance breeding efficiency. The study found significant variations across treatments, parents and parent vs. cross for all attributes related to seed yield. Some traits exhibited notable disparities between parents and crosses, underscoring the intricate genetic dynamics at play. The estimation of genetic components of variance underscored a predominant influence of non-additive gene action, especially in traits linked to yield. Specific combining ability (SCA) consistently surpassed general combining ability (GCA), underscoring the substantial role of non-additive genetic effects. Parental genotypes NPJ-194, DRMR-15-16, Kranti and NPJ-194 were identified as consistent and potent general combiners, indicating their potential to pass on favorable alleles to their offspring. Hybrid combinations such as SKJM-05 × Kranti, RW-85-59 × SKJM-05, and NPJ-194 × SKJM-05 exhibited notable GCA effects of parents, per se performance and SCA effects of hybrids for seed yield plant−1. Heterosis breeding proved to be a viable strategy, with crosses such as RW-85-59 × SKJM-05, RW-85-59 × Giriraj, RW-85-59 × PHR-2, DRMR-15-16 × Giriraj, and SKJM-05 × PHR-2 exhibiting significant positive heterosis for OC over both mid-parent and better-parent values. Overall, this research provides valuable insights into the genetic basis of morphological traits in Indian mustard, offering strategic directions for focused breeding efforts and trait refinement.